Sex differences in acute coronary syndrome management and in 12-month case-fatality trends: data from the French MONICA registries. (11th May 2022) - Gauthier, V; Montaye, M; Ferrieres, J; Huo Yung Kai, S; Biasch, K; Moitry, M; Amouyel, P; Dallongeville, J; Meirhaeghe, A
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Univ. Lille, Inserm, CHU Lille, Institut Pasteur de Lille, Santé publique France, U1167 - RID-AGE - Facteurs de risque et déterminants moléculaires des maladies liées au vieillissement, Lille, France. Background: Earlier studies, have reported sex differences in clinical presentation, management and outcomes of acute coronary syndrome (ACS) which have prompted the medical community to take actions to erase these differences. To our knowledge, there has been no recent analysis of sex difference trends in ACS management, to assess whether these differences have been attenuated over time. Aim: To assess recent sex differences trends in ACS characteristics, management and associated mortality. Methods: We assessed all men and women (aged 35-74) hospitalized for an incident (first) ACS, in the 3 distinct geographical areas covered by the MONICA registries in the north, east and south-west of France, during a 12-month period in 2006 and a 6-month period in 2016. We analyzed the patients' clinical, biochemical, electrocardiographic and care-related data, and their vital status 12 months after the ACS. Results: We analyzed 2023 incident ACSs in 2006 and 1173 in 2016. The proportion of men was three times higher than that of women in both periods. In 2016, women were younger (62.0 y in 2006 and 60.4 y in 2016; p=0.06) and men were older (57.6 y in 2006 and 59.0 y in 2016; p<0.01). Women had no longer more atypical symptoms than men in 2016. In both men and women, the proportion of patients with NSTEMI increased from 26% in 2006 to 39% in 2016 (p<0.0001), whereas the proportion of patients with unstable angina decreased from 14% in 2006 to 7% in 2016 (p<0.0001). Between 2006 and 2016, the proportion of thrombolysis fell from 10% to 1% (p<0.0001); conversely, the proportion of patients receiving angioplasty increased from 67% to 75% (p<0.001). However, men were still more likely than women to receive revascularization therapy (+19% in 2006 and +18% in 2016). Between 2006 and 2016, prescriptions of angiotensin-converting enzyme inhibitors at discharge decreased from 68% to 64% (p< 0.01), and prescriptions of statins increased from 89% to 91% (p=0.02), as did prescription of functional rehabilitation from 34% to 40% (p<0.0001). Despite these trends, platelet aggregation inhibitors, statins and functional rehabilitation were still less prescribed in women than men in 2016 (p<0.01), independently of confounders. Finally, the 12-month case fatality rate was 11% in 2006 and 10% in 2016 (p=0.15), without sex differences. Conclusions: The results of the present study evidenced an improvement over time in the management of ACS. However, although there were no longer sex differences in the patients' age and clinical presentation, women with ACS were still less likely than men to receive revascularization and pharmacological treatments in 2016.